Aqueous Flow Hydroxycarbonylation of Aryl Halides Catalyzed by an Amphiphilic Polymer-Supported Palladium–Diphenylphosphine Catalyst - Osako, Takao; Kaiser, Reinhard; Torii, Kaoru; Uozumi, Yasuhiro (Synlett, 2019)
An aqueous continuous-flow reaction system is developed for the palladium-catalyzed hydroxycarbonylation of aryl halides. Flow hydroxycarbonylation of aryl halides in aqueous solution proceeds efficiently in a flow reactor containing a palladium–diphenylphosphine complex immobilized on an amphiphilic polystyrene–poly(ethylene glycol) resin to give the corresponding benzoic acids in excellent yields.
Keywords: continuous-flow reaction; hydroxycarbonylation; aryl halides; palladium catalysis; benzoic acids; catalyst support; heterogenous catalysis